Balancing strength and electrical conductivity in recycled Al-Mg-Si alloys: Beneficial effect of combining continuous rheo-extrusion processing with Al-5Ti-1B refiner - Shuo Zhang; Qing He; Guangzong Zhang; Siqi Yin; Junwen Li; Jin Zhang; Renguo Guan (Materials & Design)
This study utilizes the continuous rheo-extrusion (CRE) process and CRE Al-5Ti-1B grain refiner to fabricate high-quality recycled Al-Mg-Si alloy wires, aiming to achieve an optimal balance between strength and electrical conductivity. The research shows that a proper extrusion roll speed (≤ 6 rpm) promotes the formation and transformation of low-angle grain boundaries (LAGBs) into high-angle grain boundaries (HAGBs), while increased shear stress induces the fragmentation of secondary phases and the formation of nano-sized secondary phases. This promotes continuous dynamic recrystallization (CDRX) and grain refinement. However, excessive speeds elevate deformation temperatures, impeding refinement and promoting grain growth. The CRE Al-5Ti-1B addition aids in CDRX and counters the adverse effects of higher temperatures. Grain refinement and increased dislocation density primarily elevate the yield strength (YS), while the increase in volume fraction of nano-sized precipitates chiefly boosts electrical conductivity. At 6 rpm with 0.4 wt.% CRE Al-5Ti-1B, the alloy wire exhibited average grain size of 8.7 μm, YS of 108.6 MPa, ultimate tensile strength (UTS) of 243.5 MPa and an electrical conductivity of 54.8 % IACS. This approach enables the production of Al-Mg-Si alloy wires with enhanced strength and conductivity, offering insights into the recycling and sustainable utilization of these materials.